Threat Analysis of The Repatriation of Ex-ISIS FTF Children to Indonesia - Ronaldo, Freddy; Nurisnaeny, Poppy Setiawati; Riyanta, Stanislaus (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
After the fall of ISIS, the repatriation of former ISIS members to their home countries has become an important issue. The international community encourages the repatriation of ex-ISIS families, especially children who have suffered in refugee camps in Syria. Likewise, the Indonesian government is still open to repatriating orphans under the age of 10. This study aims to determine the threat of repatriation of former ISIS FTF children to Indonesia, as well as intelligence strategies in anticipating the threat. This research uses a qualitative approach based on an inductive perspective. The results show that the repatriation of ex-ISIS FTF children may pose a moderate threat. The intelligence strategy to anticipate the threat is the use of tools or methods, including regulations and resource support from various institutions, equipped with the right way to achieve the goal of minimizing or eliminating threats, with a focus on early detection and early warning.